The Introvert Personality and Speaking Challenges: The Case of Indonesian EFL Student Teachers - Erlina, Dian; Pratama, Rendo Alesta; Marzulina, Lenny; Holandyah, Muhamad; Herizal, Herizal; Harto, Kasinyo (Universitas Jambi, Indonesia, 2023)
Learning to speak English is not easy. This study aimed at finding out 1) the personality of students of English Education Study Program student teachers and 2) the speaking challenges faced by the introverted student teachers at an English Education Study Program. This study used a mixed-method design. For the quantitative data, the samples were 98 students chosen by using purposive sampling. Meanwhile, for the qualitative data, there were 5 participants, and homogeneous sampling was the sampling technique. The data were collected through questionnaires, observation, and interviews. The result of the study was that 14 students had introverted personalities, and 84 students had extroverted personalities. Furthermore, the speaking challenges faced by introverted students were language components, the psychology of students, and the learning environment. This study can give a positive contribution to the students, teachers, and future researchers.